Farmers’ perception of consumer information and adoption intention towards organic rice farming: Evidence from community enterprise in rural Thailand - Harry Jay Cavite; Chanhathai Kerdsriserm; Christopher Llones; Nuttanan Direksri; Suneeporn Suwanmaneepong (Outlook on Agriculture, 2022)
Organic production has gained increased attention worldwide because of its sustainable way of producing food crops apart from its significant contribution to agricultural development. While some policies and programs encourage rice farmers to adopt organic farming, its uptake is far less than expected, particularly in the rural areas of Thailand. Hence, this study attempts to explain rice farmers’ adoption intention towards organic rice farming, drawing insights from the diffusion of innovations theory, and incorporating consumer information as an important alternative information source. A questionnaire survey was conducted among 201 community enterprise farmers using a purposive sampling technique. Results found that farmers have a generally high-level perception towards consumer information items. These items were further explored using binary logistic regression with the commonly used adoption factors. Results revealed that education level, seed input source, buying price, training attendance, and credit access significantly impacted farmers’ adoption intention. Although farmers have a generally high level of agreement towards consumer information, this factor does not affect their adoption. The findings provide critical insights to the community enterprise and policymakers to fully understand community enterprise farmers’ adoption motives and devise targeted strategies to promote widespread adoption of organic rice farming.
Keywords: Agricultural Innovations and Practices; Innovation and Socioeconomic Development; Organic Food and Agriculture